EFFECT OF DIETARY PROTECTED LYSINE SUPPLEMENTATION ON MILK YIELD, COMPOSITION AND SOME BLOOD AND RUMEN PARAMETERS IN LOCAL EWES - M., Kamal . N. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to evaluate the effect of supplementing rumen protected lysine on milk production, composition and some blood and rumen parameters. Nine local ewes were assigned into three groups (3 ewes for each) and were allocated into 3x3 Latin-square design. The first group (control) was fed concentrate diet. The second group (F-LYF) was fed the control diet and supplemented with free lysin (3g/ewe/day). The third group (P-LYS) was fed the control diet and supplemented with rumen protected lysine (3g/ewe/day). The ewes were offered 1000 g/ewe/day of concentrate and wheat straw ad libitum in addition to grazing for 6 hr per day. Results revealed that ewes supplemented with P-LYS and F-LYS had a non-significant (P>0.05), increase in daily milk yield, fat content and yield, protein yield, fat corrected milk (FCM) and energy corrected milk (ECM). The serum urea concentration was reduced significantly (p<0.05) in the (P-LYS) and (F-LYF) compared to control group, while neither protected nor free lysine affecting (P>0.05) all blood parameters as well as rumen pH and protozoa numbers, while ammonia nitrogen (NH3-N) was numerically increased (P>0.05).